Translation Techniques of Indonesia Pusaka Song Lyrics in Chinese Version on Youtube Channel - Supriyadi, Francisca Akhidnasiwi; Junining, Esti (Universitas Brawijaya, 2023)
This study examines the techniques and ideologies used to translate Indonesian Pusaka songs into the Chinese version. The object of this research is the lyrics of Indonesia Pusaka songs in the Chinese version. This study addresses two main issues, namely: (1) the techniques used in the translation of Indonesia Pusaka songs into Chinese versions and (2) the ideology underlying the translation of Indonesia Pusaka songs into Chinese versions. A descriptive qualitative approach has been adopted in this research. The listen-and-record technique is employed in this research to gather data. . The lyrics of Indonesia Pusaka in Chinese version as the primary source of data for this research. The translation of Chinese- versions of Indonesian Pusaka songs is examined using Molina and Albir translation techniques. From the research conducted, there are 8 song lyrics that all use the Linguistic Amplification translation technique. As for the translation ideology used, it is more inclined to the domestication translation ideology. This domestication translation ideology can be seen from the techniques oriented to the target language, totalling 100%.